2000
DOI: 10.1161/01.str.31.12.2930
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Does Not Influence Atherosclerotic Plaque Behavior in Patients With Established Carotid Artery Stenosis

Abstract: Background and Purpose-Research for infectious agents in the etiology of atherosclerosis has identified Chlamydia pneumoniae as a possible candidate. While there is evidence of an association between presence of this microorganism and atherosclerosis, it is unclear whether infection has a genuinely etiologic role in this disease, whether its presence influences clinical outcomes, and, if so, at which stages of disease this occurs. We have approached this issue in patients with advanced carotid artery atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Analyzing 33 studies with regard to hybridization in the detection of C. pneumoniae DNA, we found 11 studies in which only gel electrophoresis had been used to visualize PCR products (8,16,18,30,37,38,40,(42)(43)(44)(45). In the other 22 studies, PCR results were confirmed by hybridization (2, 5, 6, 12, 14, 19, 23-26, 28, 29, 31-35, 39, 47, 48, 50 …”
Section: Discussionmentioning
confidence: 99%
“…Analyzing 33 studies with regard to hybridization in the detection of C. pneumoniae DNA, we found 11 studies in which only gel electrophoresis had been used to visualize PCR products (8,16,18,30,37,38,40,(42)(43)(44)(45). In the other 22 studies, PCR results were confirmed by hybridization (2, 5, 6, 12, 14, 19, 23-26, 28, 29, 31-35, 39, 47, 48, 50 …”
Section: Discussionmentioning
confidence: 99%
“…64 Clinical data support that the presence of C pneumoniae in carotid stenoses increases local thrombogenicity and the risk of infarction, 62,81 but not all results favor this hypothesis. 65 Some [82][83][84][85] but not all 86,87 seroepidemiological studies reported an association between past C pneumoniae infection and asymptomatic carotid atherosclerosis or increased intimamedia thickness. A prospective study found an independent association between C pneumoniae seropositivity and (1) progression of the intima-media thickness and (2) ischemic events, effects that were particularly expressed in patients with increased CRP.…”
Section: Continuous Inflammation In Matured Atherosclerotic Plaquesmentioning
confidence: 99%
“…Shor et al (129) reported a strong association between atheromatous lesions and C. pneumoniae; however, minimal lesions were C. pneumoniae positive as often as severe lesions were. (147) 1999 IH N ϩ H MOMP coding ND Bartels et al (6) 1999 IH N ϩ H Cloned PstI N D Nadrchal et al (97) 1999 IH N 16S rRNA ND Thomas et al (138) 1999 IH N ϩ H MOMP coding ND Blasi et al (32) 1999 TriPure N Cloned PstI RT-PCR 16S rRNA Jantos et al (64) 1999 IH ϩ Qiagen S ϩ H 16S rRNA N MOMP coding Bartels et al (7) 2000 IH N ϩ H Cloned PstI N D Berger et al (8) 2000 IH Q-PCR 16S rRNA ND Gibbs et al (38) 2000 …”
Section: Correlation Of the Presence Of C Pneumoniae With The Degreementioning
confidence: 99%